Biological activities and chemical profile from Batis maritima (Bataceae), a halophyte species with bioprospecting potential (Research, Society and Development, 2021)
Halophytes are salt-tolerant plants, enriched in metabolic compounds with several industrial applications. Batis maritima is a halophyte with occurrence in tropical and subtropical zones and the present work aimed to investigate B. maritima leaves extract for biotechnology and bioprospecting approaches. The present study evaluated the phytochemical profile, the role of acetylcholinesterase, and protective activities from B. maritima. The phytochemical screening highlighted the presence of phenolic compounds, anthracenes, and saponins. The metal content analysis revealed sodium (Na) as the most abundant salt (1 g/kg), followed by Al (0.35 g/kg), and several other elements in lower concentrations. Further, DPPH and TAC methodologies showed an significant antioxidant activity (IC50 5.17 ± 0.05 μg/mL and 0.45 ± 0.08 mg.AAEm, respectively).  A metal chelating activity was also observed, with IC50 25.76 ± 0.3 μg/mL. Additionally, B. maritima aqueous extract disclosed an anticholinesterase inhibitory effect in a dose-dependent manner (IC50 = 0.0023 mg/mL). Haemolysis assay did not reveal any toxic effects. On the other hand, the cytotoxicity assay, using murine fibroblasts cells (NIH-3T3), showed a decrease in cell viability at high concentrations.